Use of the Khorana score to predict venous thromboembolism in patients undergoing chemotherapy for uterine cancer - Rachael N. Piver; Vincent M. Wagner; Monica D. Levine; Floor J. Backes; Laura J. Chambers; David E. Cohn; Larry J. Copeland; Casey M. Cosgrove; Christa I. Nagel; David M. O'Malley; Kristin L. Bixel (Elsevier, 2023)
Objective: Gynecologic cancers are associated with a high risk of venous thromboembolism (VTE). The Khorana score is a validated tool to assess risk of VTE in cancer patients. The purpose of this study is to determine if the Khorana score can be used as a risk stratification tool for VTE in patients with uterine cancer undergoing chemotherapy. Methods: A retrospective cohort study of patients with newly diagnosed uterine cancer receiving chemotherapy over a 4-year period was conducted. The patients were stratified based on their Khorana score as well as their chemotherapy sequence, neoadjuvant or definitive versus adjuvant. Results: A total of 276 patients were included: 40 received neoadjuvant or definitive, 236 adjuvant chemotherapy. Most patients had advanced stage disease (64.5%). 18 (6.5%) patients developed VTE within 180 days of initiating chemotherapy. High Khorana score was associated with a non-significant increase in VTE (K ≥ 2 OR 1.17, CI 0.40-3.39, K ≥ 3 OR 1.69, CI 0.61-4.69) but had poor predictive accuracy based on area under the curve (K ≥ 2 0.51, K ≥ 3 0.55). The VTE rate was higher in the neoadjuvant/definitive chemotherapy group to adjuvant (12.5% vs 5.5%, p = 0.11). While the former group had a higher average Khorana score (2.35 vs 1.93, p = 0.0048), this was not predictive of VTE. Conclusions: While validated in other cancer types, the Khorana score was found to be a poor predictor of VTE in patients with uterine cancer. The use of the Khorana score to guide routine thromboprophylaxis in these patients should be used with caution and further investigation is warranted.